Diminished PLK2 Induces Cardiac Fibrosis and Promotes Atrial Fibrillation. Issue 8 (26th August 2021) - Künzel, Stephan R.; Hoffmann, Maximilian; Weber, Silvio; Künzel, Karolina; Kämmerer, Susanne; Günscht, Mario; Klapproth, Erik; Rausch, Johanna S.E.; Sadek, Mirna S.; Kolanowski, Tomasz; Meyer-Roxlau, Stefanie; Piorkowski, Christopher; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Fibrosis promotes the maintenance of atrial fibrillation (AF), making it resistant to therapy. Improved understanding of the molecular mechanisms leading to atrial fibrosis will open new pathways toward effective antifibrotic therapies. Objective: This study aims to decipher the mechanistic interplay between PLK2 (polo-like kinase 2) and the profibrotic cytokine OPN (osteopontin) in the pathogenesis of atrial fibrosis and AF. Methods and Results: Atrial PLK2 mRNA expression was 10-fold higher in human fibroblasts than in cardiomyocytes. Compared with sinus rhythm, right atrial appendages and isolated right atrial fibroblasts from patients with AF showed downregulation of PLK2 mRNA and protein, along with increased PLK2 promotor methylation. Genetic deletion as well as pharmacological inhibition of PLK2 induced profibrotic phenotype conversion in cardiac fibroblasts and led to a striking de novo secretion of OPN. Accordingly, PLK2-deficient (PLK2 knockout) mice showed cardiac fibrosis and were prone to experimentally induced AF. In line with these findings, OPN plasma levels were significantly higher only in patients with AF with atrial low-voltage zones (surrogates of fibrosis) compared with sinus rhythm controls. Mechanistically, we identified ERK1/2 as the relevant downstream mediator of PLK2 leading to increased OPN expression. Finally, oral treatment with the clinically available drug mesalazine, known to inhibit ERK1/2, prevented cardiac OPN overexpression and reversed the pathological PLK2 knockout phenotype in PLK2 knockout mice. Conclusions: Abnormal PLK2/ERK1/2/OPN axis function critically contributes to AF-related atrial fibrosis, suggesting reinforcing PLK2 activity and/or OPN inhibition as innovative targets to prevent fibrosis progression in AF. Mesalazine derivatives may be used as lead compounds for the development of novel anti-AF agents targeting fibrosis.